Detection of Yr27 virulence in Puccinia striiformis f.sp. tritici populations on wheat in Iraq - Al-Maaroof, Emad Mahmood; Hovemoler, Mogens; Ali, Rizan; Maahood, Hazha; Naser, Azad; Muhammed, Laith (Journal of Cereal Research, 2025)
This study was conducted to detect any possible changes in virulence spectrum of Puccinia striiformis f. sp. tritici population in Iraq. Biological trap nurseries of yellow rust were planted in different locations representing most of wheat growing areas in Iraq. The plants were exposed to the natural population inoculum of the pathogen in the fields. Diseases scoring were conducted by recording disease severity and infection types on each genotype at different stages of wheat development. Yellow rust development was calculated on the local susceptible wheat cultivars Araz, and Saberbeg. Yr samples collected from the commercial wheat fields from different locations were sent to the Global Rust Center for race analyses. Virulence analysis ofÂ Puccinia striiformis f. sp. tritici Â populationÂ ,revealed detection of virulence against the known resistant genes Yr2, Yr6, Yr7, Yr9, Yr18, YrA, Yr21, Yr25, Yr27, Yr28, Yr29 and Yr31 at adult plant stage in Sulaimania, while virulence against the known resistant genes Yr1, Yr2, Yr4, Yr5, Yr7, Yr9, Yr SD, YrSu, YrND, Yr32, YrA, Yr21, Yr27, Yr28, Yr31, were detected in the natural populations of P. striiformis f. sp. tritici at adult plant stage Nineveh. Out of 34 Yr samples sent to GRRC for race analysis, 12 samples were only recovered while 22 samples were failed to be recovered. Breakdown of resistant genes Yr27 and Yr25 was further confirmed at seedling stage. Infection rate value of yellow rust during the epidemic on Saber Beg (r- value= 0.337) was higher than Araz (0.187). Keywords: Yellow Rust, Triticum aestivum, Resistant genes, Pathogen variability, Iraq